Contract management practices in World Bank and PPR 2008 : a comparative study - Tanveer, S. M. Sadik (BRAC University, 2013)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2013.